2015
DOI: 10.1007/s10534-014-9819-3
|View full text |Cite
|
Sign up to set email alerts
|

Roles of oxidative stress and endoplasmic reticulum stress in selenium deficiency-induced apoptosis in chicken liver

Abstract: Oxidative stress and endoplasmic reticulum (ER) stress are involved in different types of stress-induced injuries. The aim of the present study was to evaluate the effect of Se deficiency on oxidative stress, ER stress and apoptosis in chicken livers. Chickens (1 day old, n = 180) were randomly divided into two groups: the L group [fed with a Se-deficient (Se 0.033 mg/kg) diet] and the control group [fed with a normal (Se 0.2 mg/kg) diet]. Factor-associated oxidative stress, catalase (CAT) activity, H2O2 produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…These complicated processes involve acquisition, sequestration, and efflux of metal ions [51]. Selenium occurs naturally in the Earth’s crust; and at low concentration it is essential for living organisms [52]. Under aerobic conditions, this trace element exists as selenite and selenate, and at high levels these salts can be toxic and mutagenic to bacteria [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These complicated processes involve acquisition, sequestration, and efflux of metal ions [51]. Selenium occurs naturally in the Earth’s crust; and at low concentration it is essential for living organisms [52]. Under aerobic conditions, this trace element exists as selenite and selenate, and at high levels these salts can be toxic and mutagenic to bacteria [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium occurs naturally in the Earth’s crust; and at low concentration it is essential for living organisms [52]. Under aerobic conditions, this trace element exists as selenite and selenate, and at high levels these salts can be toxic and mutagenic to bacteria [52,53]. High selenite-resistant bacterial strains like Ralstonia metallidurans CH34 possess the ded A gene that regulatesselenite uptake [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Se deficiency induced oxidative stress, apoptosis, and inflammatory response, which were accompanied by the upregulation of typical injury biomarkers such as NO, caspase-3, NF-κB, and iNOS in different tissues and organs [27][28][29]. However, the effect of Se deficiency on chicken erythrocytes is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…As an essential trace mineral22, selenium (Se) plays an important role in suppressing oxidative stress232425 and has been proved interrelationship with DNA damage and oxidative stress26. Se deficiency may induce oxidative stress and endoplasmic reticulum stress27 in some special cases (such as the use of ECMO)28. In contrast, Se’s essential interrelationship with coenzyme Q10 in cardiovascular diseases29 and its preventive effect in combination with vitamin E for prostate cancers30 suggested a great potential for the prevention of ONFH.…”
mentioning
confidence: 99%